1994
DOI: 10.1016/0020-7292(94)90071-x
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal endometrial hyperplasia: role of danazol therapy

Abstract: Although 17.1% of the women had a persistence of the hyperplasia and 8.4% of the symptom-free women relapsed after 4 months of follow-up, this experience confirms the effectiveness of danazol therapy in hyperplastic endometrial lesions. Nevertheless, a study comparing danazol and progestin therapy is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Other studies have suggested danazol causes glandular atrophy and a pseudodecidual change of the endometrium [5,6,17]. We speculate in the present study that locally released danazol from the D-IUD had direct beneficial effects on endometrial hyperplasia through topical application due to the mechanism of diffusion and through a blood-borne mechanism due to the hypervascularity of the uterine cervix, and induced glandular atrophy and a pseudodecidual change of the endometrium.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Other studies have suggested danazol causes glandular atrophy and a pseudodecidual change of the endometrium [5,6,17]. We speculate in the present study that locally released danazol from the D-IUD had direct beneficial effects on endometrial hyperplasia through topical application due to the mechanism of diffusion and through a blood-borne mechanism due to the hypervascularity of the uterine cervix, and induced glandular atrophy and a pseudodecidual change of the endometrium.…”
Section: Discussionsupporting
confidence: 50%
“…Although the recurrence rate in the patients with endometrial hyperplasia (groups A and B) in the follow-up was 20%, this rate is acceptable as compared with other studies [8,16,17]. In addition, 2 patients conceived after removal of D-IUD.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…When danazol has been clinically applied to patients with functional uterine bleeding (24) or endometrial hyperplasia lesions (25)(26)(27)(28)(29)(30)(31), danazol may act on endometrial lesions by inhibiting endogenous estrogen and by progestin-like functions. However, during local danazol therapy it seems likely that unknown direct actions of danazol regulate endometrial cell growth locally and directly.…”
Section: Introductionmentioning
confidence: 99%